Pretransplant C-reactive protein as a prognostic marker in allogeneic stem cell transplantation: A PRISMA-compliant meta-analysis. Issue 8 (February 2019) - Wu, Peilin; Liang, Wei; Chen, Xianying; Chen, Lihong; Yang, Xuerong; Yan, Zhengwei; Wang, Wei
Abstract: Background: Numerous reports have explored the prognostic value of pretransplant serum C-reactive protein (CRP) in patients receiving allogeneic stem cell transplant (ASCT), but the results remain conflicting. Therefore, we performed a meta-analysis to comprehensively assess the prognostic value of pretransplant serum CRP in patients receiving ASCT. Methods: We systematically searched eligible studies in PubMed, Embase, and Web of Science from 1999 to September 2018. The pooled hazard ratios (HRs) and their corresponding 95% CIs were used to synthetically assess the prognostic value of pre-ASCT CRP in terms of overall survival (OS), non-relapse mortality (NRM), and acute graft versus host disease (aGVHD). Results: A total of 14 articles with 15 studies containing 3458 patients were included in this meta-analysis. The pooled results showed that high pre-ASCT CRP level was significantly related to worse OS (HR = 1.63; 95% CI: 1.34–1.98; P  < .05), to an increased risk of NRM (HR = 2.06; 95% CI: 1.62–2.62; P  < .05), and aGVHD (HR = 1.35; 95% CI: 1.07–1.71; P  < .05). Additionally, sensitivity and subgroup analyses demonstrated that our pooled results were stable and reliable. Conclusions: High pre-ASCT serum CRP was significantly associated with worse OS, as well as higher risk of NRM and aGVHD. CRP may be a candidate factor of updating the existing risk scoring systems or establishing a novel risk scoring systems, which has the potential of guiding patient selection for ASCT and proceeding with risk-adapted therapeutic strategies. However, more high-quality clinical studies and basic research are required to further validate our findings in view of several limitations in our meta-analysis.